PENGARUH INSENTIF DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT HAMPARAN ORIONHASIL OPTIMAL - tianto, Sep; Kristanti, Silvie; Yanti Purba, Purnama; Claudia Yosephine Simanjuntak, Demak (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research aims to know the influence of incentives and job satisfaction on performance of employees of PT Hamparan Orion Hasil Optimal. The existence of the phenomenon of the granting of incentives are not evenly distributed among employees who have long worked with the new work, the number of employees who resign, and employees did not achieve the sales target in the year 2017 aspects influenced the research. The method used is multiple linear regression analysis. The number of samples in the study were 95 employees. The results showed that the incentives and employee satisfaction employees partially affect the performance. Incentives and job satisfaction also affects the performance of employees simultaneously.